Microstructural packing- and rheology-based binder selection and characterization for Ultra-high Performance Concrete (UHPC). (January 2018) - Arora, Aashay; Aguayo, Matthew; Hansen, Hannah; Castro, Cesar; Federspiel, Erin; Mobasher, Barzin; Neithalath, Narayanan
Abstract: This paper reports strategies to design the binder phase of ultra-high performance concretes (UHPC) from commonly available cement replacement (fly ash, slag, microsilica, metakaolin) and fine filler (limestone) materials. A packing algorithm is used to extract the number density, mean centroidal distance, and coordination number of the microstructure. Similarly, rheological studies on the pastes provide yield stress, plastic viscosity, and min-slump spread. The selection criteria involves using the three microstructural and three rheological parameters individually or in combination to define packing and flow coefficients. The selection criteria is flexible enough to allow users modify the constraints depending on the application. In this study, only ternary and quaternary blends, with a total cement replacement of 30% by mass are selected for further characterization. The highly efficient microstructural packing in these mixtures and better workability that facilitated dispersion of particles to enhance the reactivity results in beneficial pore structure and mechanical properties.